Streamlining sustainable design in building information modeling BIM-based PV design and analysis tools. (2nd November 2021) - Lin, Qihang; Kensek, K.; Schiler, M.; Choi, J.
Abstract : The current BIM-based PV system design process largely depends on transferring a model to special PV simulation software. Critical geometric information is often lost during this process. An automatic PV system design and management tool was developed, which fully integrates the existing and future information of PV systems in a building information modeling (BIM) platform. This tool, PV Link, first analyzes the solar radiation on a building geometry. Then, it automatically places the PV panel based on the solar analysis and user-defined variables like PV size, roof geometry, and rooftop equipment. Finally, the solar radiation on each panel and the electricity produced are calculated and results shown in a building information model. Several case studies show it can design systems efficiently. With the information-rich BIM model, real-time analysis and management of the PVs are feasible to maintain the performance of the PV system in operation. In response to an issue raised by one of the reviewers, there is an additional discussion of the nature of science and applied science.